Radiological Evaluation of Cochlear Orientation and Its Implications in Cochlear Implantation - Kiran, Avvaru Satya (Indian J Otolaryngol Head Neck Surg, 2017)
To test whether there are variations in cochlear orientation with respect to age and sex, and its relevance in cochlear implant surgery. Implant otologists rely upon the anatomic landmarks including the facial recess and round window niche and round window membrane for accessibility and placement of electrode array into scala tympani of basal turn of cochlea. Anecdotally, surgeons note variations in cochlear orientation with respect to age. Cochlear orientation studied radiologically by pre-operative CT scan of temporal bone can guide a Surgeon’s approach to cochlear implantation. To investigate the changes in cochlear orientation with respect to age and sex; and its relevance in cochlear implantation. A retrospective analytical study was performed on CT scans of temporal bones in patients (of our hospital from July 2013 to January 2015 i.e. for a period of 18 months) with no congenital or radiological abnormalities of cochlea. The basal turn angulations of cochlea varied with age and majority of change occurred during early age. The basal turn angulations of cochlea in difficult situations during cochlear implantation were correlated with the data. There is a significant variation in cochlear orientation as measured radiologically by basal turn angulations relative to midsagittal plane. The more obtuse and acute basal turn angulations have implications like difficulty in cochleostomy and electrode placement during cochlear implantation.